Professional pedagogical activity of mathematics teacher on the basis of innovative approaches to teaching - A.A.Ergashev; O‘. M.Turdimatova (International Journal on Integrated Education, 2023)
In the article the analysis of psychological, pedagogical and methodical researches of the problem of improvement of professional training of the future teacher of mathematics in pedagogical university is considered. It shows that professional pedagogical activity is integrative, includes both traditional and innovative components of pedagogical activity.